XÁC ĐỊNH LUẬT PHÂN BỐ XÁC SUẤT CỦA DỮ LIỆU CHẤT LƯỢNG KHÔNG KHÍ ĐƯỢC QUAN TRẮC TẠI HÀ NỘI - Thị Hồng Nhung, Chử; Trung Dũng, Nghiêm (Vietnam Journal of Science and Technology, 2017)
A study to determine the probability distribution of air quality data measured at Hanoi was conducted using the statistical software of SPSS. Data used are hourly average concentrations of air  pollutants  including  SO2,  NO2,  CO,  O3,  TSP  and  PM10  collected  from  Lang  automatic ambient air quality monitoring  station, Hanoi  for a period of about 8 years,  from  July 2002  to May 2010. Obtained  results show  that  the Weibull distribution was fitted  to  the data of hourly average concentrations of  these air pollutants. As a result, Probability Density Function (PDF), f(x) and Cumulative Distribution Function (CDF), F(x) for these set of data were determined.